Social Media Usage of Higher Secondary School Students - A Pilot Study - et. al., Jijish Elias, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the context of the lock down due to Covid-19, usage of mobile phones has increased among the adolescents. Usage of mobile phones for educational purposes as well as for entertainment makes them more addicted to mobile phones and electronic gadgets. In this scenario, Nomophobia, that is fear towards the situation when there is no phone, has increased among the adolescent. In this study, investigators developed and standardized a Nomophobia rating scale (NPRS) to identify the addiction rate of Higher Secondary school students to mobile phones. NPRS applied to 82 Higher Secondary School students and the study shows that most of the students are prevalent to nomophobia. But the nomophobic rate do not depend on their locality, gender, course stream, but depend on management of school.